Establishment of Universiti Muhammadiyah Malaysia (UMAM) in the perspective of communication for development through education modernization - Amallah, Nurlaillah Sari; Bakti, Andi Faisal; Praptiningsih, Novi Andayani; Sanjaya, Makroen; Hermansah, Tantan (Informasi, 2023)
Muhammadiyah is considered a radical conservative movement among the Malaysian Muslim community. The education system in Malaysia is generally exclusive. The majority of Malaysian society is resistant to the Muhammadiyah sect except in certain states. This research used the theory from Servaes and Malikhao, the modernization paradigm that influenced academia from 1945 to 1965 was supported by the transition of socio-political technology and culture from advanced societies to traditional societies. Development is explained as economic growth. The main idea in the modernization perspective shows that development is interpreted as first, planned, and overlapping. The results showed ideologically, the principle of progressive Muhammadiyah in establishing Universiti Muhammadiyah Malaysia (UMAM) cannot be separated from the role of the 47th Muktamar Muhammadiyah in Makassar. The congress was aimed at strengthening Muhammadiyah's Islamic vision, namely progressive Islam. Muhammadiyah launched an internationalization program, especially in the field of education, one of its implementations was by developing excellent educational centers abroad. Furthermore, Malaysia is considered the first step as a representative city center that excels in education and internationalization. Muhammadiyah is a movement that cares about Muslims so that they are not degraded by the progress of other nations, so public schools were founded and eventually became universities. This research concluded that the establishment of UMAM was a place to prove that Muhammadiyah is a progressive da'wah movement and builds society towards enlightenment. UMAM presents a superior lecture system with international standards through the use of technology. However, life is still based on Islamic values.